1998
DOI: 10.1002/(sici)1097-0231(19980930)12:18<1236::aid-rcm318>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Angle and energy distributions of neutral atoms sputtered from Ni3Al(100)

Abstract: The energy and angular distributions of Ni and Al atoms sputtered from Ni 3 Al(100) by 8 keV Ar have been measured using multiphoton resonance ionization detection. The Al atoms, which originate entirely from the top atomic layer of Ni 3 Al(100), are predominantly sputtered along close packed <110> directions. On the other hand the sputtered Ni flux, which arises from both the first and second layers, has a large component normal to the surface. Molecular dynamics computer simulations agree well with experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Another experiment could be considered where the voltage is just above this threshold, so that additional subsurface contributions could start to take place. The experimental and MD study of angle and energy distributions of neutral atoms sputtered from Ni 3 Al(100) by 8 keV Ar þ ion bombardment [11] showed that the Al atoms are predominantly sputtered along close-packed h110i directions, in agreement with our results that for subsurface events the minimum E sp occurs along h110i directions (table 1).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another experiment could be considered where the voltage is just above this threshold, so that additional subsurface contributions could start to take place. The experimental and MD study of angle and energy distributions of neutral atoms sputtered from Ni 3 Al(100) by 8 keV Ar þ ion bombardment [11] showed that the Al atoms are predominantly sputtered along close-packed h110i directions, in agreement with our results that for subsurface events the minimum E sp occurs along h110i directions (table 1).…”
Section: Discussionsupporting
confidence: 89%
“…In the context of sputtering at the Ni 3 Al(100) surface, King et al [11] conducted an experimental and MD study of the energy and angular distributions of Ni and Al atoms sputtered by 8 keV Ar þ ions. However, sputtering by electron bombardment is different in at least two respects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several cases the sensitivity has proven to be sufficiently high to compile accurately energy distributions, even with angular resolution. [9][10][11][12][13][14][15][16][17]22,24 However, the determination of population partitions is much less straightforward and previous attempts to determine the population of thermally produced atoms on metastable states using onecolor two-step ionization were far less successful. In such schemes, atoms originally in different metastable states finally end up in different continuum states.…”
Section: A Evaluation Of the Experimental Proceduresmentioning
confidence: 99%
“…Little research has been undertaken on single crystal alloys. King et al have investigated angular distributions of Ni and Al atoms sputtered from the {1 0 0} plane of the Ni 3 Al alloy with an fcc structure [14]. They addressed the depth of origin of atoms sputtered from the single crystal alloy.…”
Section: Introductionmentioning
confidence: 99%